Making 3D Learning Media by Utilizing Pop Up Book as a Form of Collaboration with Teachers in SDN Triwung Kidul 1 Probolinggo City - Ani Anjarwati; Adella Pramesti; Inayatul Karimah; Violitha Volvariella; Dea Nanda (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
The teacher acts as a creator in the teaching and learning process, namely acting as a person who is able to create good, interesting and efficient learning conditions. In the learning process, learning media has an important role in achieving optimal learning. This service aims to collaborate with teachers to minimize non-optimality in the learning process. The form of collaboration that is carried out is to create 3D learning media with the theme of cultural diversity which can be used as simple media in the learning process. Pop up book learning media will later be applied to class IV SDN Triwung Kidul 1. This service activity is carried out in 3 stages, namely planning, implementation and evaluation. The preparation stage begins with observing, interviewing and preparing an activity plan. Furthermore, at the implementation stage the researcher made a collaborative project in the form of learning media pop up books as learning media. The results evaluation stage is to reflect and prepare a report so that it becomes evidence of the implementation collaboration project with SDN Triwung Kidul 1. The result of this dedication is pop up book learning media is able to overcome school constraints in the limitations of teaching materials in the learning process.